ANALISIS KANDUNGAN KADMIUM (Cd) DALAM UDANG WINDU (Penaeus monodon) YANG BERADA DI TAMBAK SEKITAR TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH KELURAHAN TERJUN KOTA MEDAN TAHUN 2014 - Yulia Khairina Ashar; evi naria; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
Exposure of heavy metals from various sources into aquatic environment will have a negative impact to aquatic organisms, even below threshold limited value. Open dumping management system that is used on landfill site at Kelurahan Terjun could cause the exposure of one of toxicant heavy metal, Cadmium (Cd), through the leachate to the shrimp farm located near the landfill site. The exposure of this toxicant heavy metal could harmfully affect aquatic organisms around the landfill site. The purpose of this study was to analyze the cadmium concentrations in shrimp samples collected from the shrimp farm, located near the landfill site. The study location in shrimp farm near landfill site at Kelurahan Terjun Kota Medan. The type of this study was descriptive, samples of this study were shrimps and water of shrimp farm which were collected in certain range :13 m, 57 m and 82 m from the landfill site. Data were analyzed descriptively in tables and naration. The study found that concentrations of cadmium in these contaminated water was 0,01296 mg/L to 0,01474 mg/L, higher than threshold limited value, while rates of cadmium accumulation on shrimp were measured at 0,12951 mg/kg, approximately equivalent to the minimum risk concentration. The shrimp accumulated cadmium concentration, commensurate with increases in the concentration of cadmium in water and the duration of exposure. Accumulation of heavy metals  in aquatic organisms such as shrimp needed continuous monitoring and surveillance owing to biomagnifying potential of toxic heavy metals (Cd). Suggested to Kota Medan government was to change management system that is used on landfill site with sanitary landfill system.